Alcohol Consumption, Brain Amyloid-β Deposition, and Brain Structural Integrity Among Older Adults Free of Dementia - Koch, Manja (J Alzheimers Dis, 2020)
BACKGROUND: Light to moderate alcohol consumption has been variably associated with lower or higher risk of dementia, but effects on Alzheimer’s disease pathology are less clear. OBJECTIVE: We determined whether late-life alcohol consumption was associated with Alzheimer’s disease pathology among older adults. METHODS: We assessed the associations of alcohol consumption self-reported in 2000–2002 with brain amyloid-β deposition on PET scans, and white matter lesion and hippocampal volume on MRIs measured 7–9 years later in 189 participants of the Ginkgo Evaluation of Memory Study (age 75–87 years at baseline) who were free of clinical dementia, using multivariable-adjusted and inverse probability-weighted robust linear regression models. RESULTS: Alcohol consumption was not statistically significantly associated with amyloid-β deposition (standardized uptake value ratio difference per drink: –0.013 [95%CI: –0.027, 0.002]). Both non-drinkers and participants consuming ≥1 drink(s)/week had higher white matter lesion volume (% intracranial volume) than did the reference group of those consuming <1 drink/week (differences: 0.25 % [95%CI: 0.01, 0.50]; 0.26 % [95%CI: 0.02, 0.50]). The association of alcohol consumption and hippocampal volume was modified by age (p = 0.02). Among participants younger than 77 years, participants consuming 1–7 drinks/week had larger hippocampal volume compared with participants consuming <1 drink/week. CONCLUSIONS: Alcohol consumption was not statistically significantly associated with amyloid-β deposition 7–9 years later. Non-drinking and greater alcohol consumption were associated with higher white matter lesion volume compared with drinking <1 drink/week. Moderate drinking was associated with higher hippocampal volume in younger individuals. Given the selective nature of this population and adverse health effects of excessive alcohol consumption, these findings warrant further investigation, but cannot be translated into clinical recommendations.